2017
DOI: 10.1002/lno.10640
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of zooplankton to methane supersaturation in the oxygenated upper waters of the central Baltic Sea

Abstract: We report on methane enrichments that were observed during summer in the upper water column of the Gotland Basin, central Baltic Sea. In the eastern part of the basin, methane concentrations just below the thermocline varied between 15 nM and 77 nM, in contrast to the western part where no methane enrichments could be detected. Stable carbon isotope ratios of methane (d 13 C-CH 4 of 267.6&) indicated its in situ biogenic origin from CO 2 reduction, which was supported by clonal sequences that clustered with Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 80 publications
7
76
0
Order By: Relevance
“…Stable carbon isotopes indicated an in situ biogenic methane origin, whereas clonal sequences pointed towards methanogenic Archaea as potential producers (Schmale et al, 2018). It was further shown that zooplankton-associated methane production contributed to the subthermocline methane enrichment (Schmale et al, 2018). The authors suggested that changes in the copepod community and food web structure influenced the spatial heterogeneity of methane accumulation in the upper part of the 20 water column.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Stable carbon isotopes indicated an in situ biogenic methane origin, whereas clonal sequences pointed towards methanogenic Archaea as potential producers (Schmale et al, 2018). It was further shown that zooplankton-associated methane production contributed to the subthermocline methane enrichment (Schmale et al, 2018). The authors suggested that changes in the copepod community and food web structure influenced the spatial heterogeneity of methane accumulation in the upper part of the 20 water column.…”
mentioning
confidence: 92%
“…Then the phytoplankton, which remained in the bottle, was sampled. The target copepod T. longicornis has been known to migrate diurnally from the light-penetrated surface layer towards greater depths to escape predation (Hansen et al, 2006;Schmale et al, 2018). For lipid biomarker studies, a concentrated sample of zooplankton rich in T. longicornis was retrieved, avoiding 30 major co-sampling of phytoplankton.…”
Section: Plankton Community and Lipid Biomarker Analysesmentioning
confidence: 99%
See 3 more Smart Citations